Developing and demonstrating an atomistic and holistic model of anthropometric failure among children under five years of age using the National Family Health Survey (NFHS)-5 data from India - Nandeep, E. R.; Jaleel, Abdul; Reddy, P. Bhaskar; Geddam, J. J. Babu; Reddy, Samarasimha N.; Hemalatha, Rajkumar (Frontiers in Nutrition, 2024)
Introduction Composite Index of Anthropometric Failure (CIAF) and its further modifications have not incorporated all the combinations of malnutrition. We propose a new model incorporating all the forms of malnutrition among children under five years of age. However, the current models might misclassify a growing child as malnourished. Our objective is to develop a comprehensive scoring system using the three anthropometric Z-scores [height-for-age (HAZ), weight-for-age (WAZ), and weight-for-height (WHZ) Z-scores] and demonstrate the proposed CIAF model using the National Family Health Survey-5 (NFHS-5) data from India. Methods A new scoring system was developed using the WAZ, HAZ, and WHZ scores to determine the child’s nutritional status. We also proposed a new CIAF model by including all possible categories of malnutrition and practically demonstrated it using the NFHS-5 dataset after applying the new scoring system. Under-five children with heights, weights, and ages available were included in the analysis. The groups of malnutrition are presented as weighted proportions before and after applying the new score to the proposed model. Results Our final analysis included individual-level data of 198,802 children under five years of age (weighted N = 195,197). After applying the new scoring system to the proposed model, the prevalence of stunting has reduced to 11.8% (95% CI 11.66–11.94) from 13.2% (95% CI 13.09–13.39) and wasting prevalence has reduced to 4.9% (95% CI 4.85–5.04) from 6.4% (95% CI 6.29–6.51). The most common forms of anthropometric failures among Indian children by using the newly developed CIAF model are: “Stunting and underweight” (30,127; 15.4%), Stunting only (23,035; 11.8%), and “wasting and underweight” (14,698; 7.5%). We found a new category called “Stunting, underweight, and overweight” (stunting = HAZ < −2SD, underweight = WAZ < −2SD, overweight = WHZ > +2SD). It constituted 0.1% (220 children) of the total sample. Conclusion When the new scoring system is applied to the proposed CIAF model, it captures all forms and combinations of malnutrition among under-five children without overlap and prevents misclassifying a growing child as malnourished. The newly identified category shows that stunting (HAZ < −2SD), overweight (WHZ > +2SD) and underweight (WAZ < −2SD) can co-exist in the same child.